Exploring the conscious and unconscious processes of internalised racism in the therapeutic relationship: a thematic analysis - Ellis, Emma (Auckland University of Technology, 2015)
This dissertation asks how the internalised racism of racial minority clients becomes identified and treated clinically by white psychotherapists. Four psychotherapists, who self-identified as white, participated in semi-structured interviews, exploring their perceptions and understandings of how internalised racism and racism manifested within the clinical setting. The data from these interviews was analysed using thematic analysis and produced four main themes; ‘manifestations of internalised racism and racism in therapy’, ‘dis-identification’, ‘therapist’s explicitness’ and ‘connection to culture’. These themes were supported and anchored by four sub-themes. The themes represent a therapeutic process called: emergence, understanding, intervention and aim. The emergence of ‘racism and internalised racism in therapy’ describes both the clients’ and the psychotherapists’ experiences of internalised racism and racism as it emerges in the therapeutic encounter. ‘Dis-identification’ captures the psychotherapists’ understanding of internalised racism operating as their minority client’s dis-identification with their racial and cultural heritage. ‘Therapist’s explicitness’ identifies a therapeutic intervention, the psychotherapist’s communication to their minority clients about the racial differences between them. And finally ‘connection to culture’ captures the psychotherapist’s therapeutic aim of encouraging a connection to racial and cultural heritage as a protective factor against racism and emotional and psychological difficulties.
Keywords: Internalised racism; Racism; Psychotherapy; Psychotherapists